Agreement of Colposcope and Gynocular in Assessment of Cervical Lesions by Swede Score: A Randomized, Crossover Pilot Trial - Ngonzi, Joseph; Bajunirwe, Francis; Wistrand, Charlotte; Mayanja, Ronald; Altman, Daniel; Thorsell, Malin; Shemer, Elisabeth Andrea Wikstrom (Journal of lower genital tract disease, 2013)
Objective. This study aimed to determine if criterion standard colposcopy could be provided by a pocket-sized battery-driven colposcope, the Gynocular. Materials and Methods. The study was a randomized, crossover, pilot clinical trial for evaluating agreement of diagnosis of cervical lesions by colposcopy using a standard colposcope and a pocket-sized battery-driven colposcope, the Gynocular, in 69 women positive for visual inspection with acetic acid. Swede scores were used at the time of colposcopy and compared with the final histological diagnosis after directed cervical biopsy. To test the level of agreement between the colposcopy and Gynocular, we calculated the percentage agreement and the J statistic. We calculated the detection rates of cervical lesions of the Gynocular and a standard colposcope using biopsy results as criterion standards. All included patients also underwent a Pap smear. Results. The level of agreement of Swede score between the Gynocular and colposcope was 70.1% and the J statistic was 0.65 (p G .001). Biopsy identified 4 women (6.7%) with cervical intraepithelial neoplasia 1 (CIN 1) and 1 woman (1.7%) with CIN 2; 2 women (3.4%) had CIN 3, and 2 women had invasive cervical cancer (CIN 3+). Pap smear detected 2 women (3.1%) with CIN 1 but did not identify any highgrade cervical lesion. Cervicitis was present in 17 (27.4%) of the Pap smears and in 34 (57.6%) of the biopsies. Conclusions. The study shows that in visual inspection with acetic acid Ypositive women, a battery-driven, pocketsized colposcope has a significant level of agreement with stationary colposcopy in assessing cervical lesions.
Keywords: cervical cancer; colposcopy; cervical lesions; cytology; biopsy; Swede score; Gynocular